The genetics of FAP and FAP-like syndromes. - Lipton, L; Tomlinson, I (2006)
The presence of multiple adenomatous polyps in the large bowel confers a high lifetime risk of colorectal cancer. Although many cases of classical familial adenomatous polyposis (> 100 polyps) can be accounted for by mutations in the adenomatous polyposis coli (APC) gene, a large group of patients remains with multiple (5-100) adenomas and in whom there is no detectable APC mutation. Recently two new genetic variants have been found to be associated with multiple colorectal adenomas and cancer, MYH/MUTYH on chromosome 1p and the HMPS/CRAC1 locus on chromosome 15q13-q14. New information also continues to emerge regarding the less common hamartomatous polyposis conditions, Peutz-Jeghers syndrome and Juvenile Polyposis syndrome. In approximately half to two thirds of these families, germline genetic variants can now be uncovered. In this review we draw together some of the most recent information pertinent to the molecular pathogenesis of colorectal polyposis.